The environment for women in physics in Ireland - MCCABE, EITHNE (AIP, 2015)
P hysics is contributing strongly to the national Irish economy , with 4.5% of the Irish workforce employed in physics - based or other science, technology, engineering, and math ( STEM ) sectors. However, a recent national report reveals that the proportion of women working in jobs that utilize STEM skills is less than 25 % of the workforce. We present d ata collected from the views of 1,000 female secondary school students, young women (age 18 – 23), secondary - school teachers and parents on what influences secondary school students’ choices of subjects and in particular STEM - related subjects . In addition, b enchmarking data on female student and staff ratios for the past five years is presented from all seven Irish u niversity p hysics d epartments
AIP Conf. Proc.
American Institute of Physics Conference Series: WOMEN IN PHYSICS: 5TH IUPAP INTERNATIONAL CONFERENCE ON WOMEN IN PHYSICS
Keywords: Inclusive Society; Nanoscience & Materials